THE INFLUENCE OF COMPENSATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT TUNAS DWIPA MATRA PALOPO CITY BRANCH - Ardhana, Muhammad Anugrah; Baso , Nurfatima Azzahra; Saputra , Putu Dimas; Wisnaini, Wisnaini; Irianti, Irianti; Sule , Lifran; Munawir, Munawir (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the effect of compensation and work environment on employee performance at PT. Tunas Dwipa Matra Palopo branch. The research method used is quantitative with data collection techniques through questionnaires. The research sample consisted of 40 employees. Data analysis techniques using multiple linear regression with SPSS 25. The results showed that simultaneously compensation and work environment have a positive and significant effect on employee performance with a significance value of 0.001 < 0.05. Partially, the work environment has a positive and significant effect on employee performance (sig = 0.001), while compensation has no significant effect (sig = 0.474). The R Square value of 0.745 indicates that 74.5% of employee performance variability can be explained by compensation and work environment.